2017
DOI: 10.1038/s41598-017-08258-6
|View full text |Cite
|
Sign up to set email alerts
|

Indirect genetic effects: a key component of the genetic architecture of behaviour

Abstract: Behavioural ecology research increasingly focuses on why genetic behavioural variation can persist despite selection. Evolutionary theory predicts that directional selection leads to evolutionary change while depleting standing genetic variation. Nevertheless, evolutionary stasis may occur for traits involved in social interactions. This requires tight negative genetic correlations between direct genetic effects (DGEs) of an individual’s genes on its own phenotype and the indirect genetic effects (IGEs) it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 61 publications
1
67
2
Order By: Relevance
“…; Santostefano et al. ). As we failed to detect significant covariance between DGEs and IGEs (COV Ad,Ai ) in the two density treatments, the evolutionary response of aggression in the group of unrelated individuals will be greater in the high‐density environment due to large DGEs (assuming that similar selection acts between density environments).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…; Santostefano et al. ). As we failed to detect significant covariance between DGEs and IGEs (COV Ad,Ai ) in the two density treatments, the evolutionary response of aggression in the group of unrelated individuals will be greater in the high‐density environment due to large DGEs (assuming that similar selection acts between density environments).…”
Section: Discussionmentioning
confidence: 98%
“…Our recent research has demonstrated that IGEs significantly contribute to variance in aggression in this species (Santostefano et al. ). In addition, developmental density influences maturation time, survival, and body mass in this species (Iba et al.…”
mentioning
confidence: 95%
See 3 more Smart Citations